Maize Autophagy-Related Protein ZmATG3 Confers Tolerance to Multiple Abiotic Stresses - Mengli Liu; Li Ma; Yao Tang; Wangjing Yang; Yuying Yang; Jing Xi; Xuan Wang; Wanchao Zhu; Jiquan Xue; Xinghua Zhang; Shutu Xu (Plants)
Abiotic stresses pose a major increasing problem for the cultivation of maize. Autophagy plays a vital role in recycling and re-utilizing nutrients and adapting to stress. However, the role of autophagy in the response to abiotic stress in maize has not yet been investigated. Here, ZmATG3, which is essential for ATG8-PE conjugation, was isolated from the maize inbred line B73. The ATG3 sequence was conserved, including the C-terminal domains with HPC and FLKF motifs and the catalytic domain in different species. The promoter of the ZmATG3 gene contained a number of elements involved in responses to environmental stresses or hormones. Heterologous expression of ZmATG3 in yeast promoted the growth of strain under salt, mannitol, and low-nitrogen stress. The expression of ZmATG3 could be altered by various types of abiotic stress (200 mM NaCl, 200 mM mannitol, low N) and exogenous hormones (500 µM ABA). GUS staining analysis of ZmATG3-GUS transgenic Arabidopsis revealed that GUS gene activity increased after abiotic treatment. ZmATG3-overexpressing Arabidopsis plants had higher osmotic and salinity stress tolerance than wild-type plants. Overexpression of ZmATG3 up-regulated the expression of other AtATGs (AtATG3, AtATG5, and AtATG8b) under NaCl, mannitol and LN stress. These findings demonstrate that overexpression of ZmATG3 can improve tolerance to multiple abiotic stresses.